Model and gear shifting control of a novel two-speed transmission for battery electric vehicles. (October 2020) - Tian, Yang; Zhang, Nong; Zhou, Shilei; Walker, Paul D.
Highlights: Modelling the electric drive system equipped with the two-speed planetary automated manual transmission (PAMT). Devising the gear shifting control system and proposing three alternative candidate torque trajectories for the first stage and the fifth stage of the gear shifting process. Validating their impacts on the vehicle jerk and shift durations and exploiting the optimal candidate torque trajectory. Abstract: Integrating a multispeed transmission into the electric drive system provides the potential of ulteriorly improving the overall efficiency of battery electric vehicles (BEVs). In this paper, we propose a novel two-speed planetary automated manual transmission (PAMT) which features a more compact mechanical structure than clutchless automated manual transmission (CLAMT) and easier gear shifting control than power-on transmissions. To present the transient behaviours during the gear shifting, a detailed and original dynamical model of the electrified powertrain is developed, including an electric machine (EM), a two-speed PAMT, synchronizer mechanisms, driveline and vehicle, etc. Afterwards, the gear shifting control system is devised, and the gearshift process is orderly divided into five stages based on the proposed control strategy. Next, three alternative planning torque trajectories, i.e., the third-degree polynomial (TDP), the fifth-degree polynomial (FDP) and the seventh-degree polynomial (SDP), are proposed to control the EM torque at the first and the fifth stages of the gear shifting respectively. Subsequently, a series of simulations are performed to validate which candidate torque trajectory is capable of achieving the optimal gear shifting quality in term of reducing the longitudinal vehicle jerk and shift durations. This study provides a beneficial reference for the development of BEVs' transmission system.